Subspecialization of R2R3-MYB Repressors for Anthocyanin and Proanthocyanidin Regulation in Forage Legumes - Albert, Nick W. (Frontiers in Plant Science, 2015)
The synthesis of anthocyanin pigments and proanthocyanidins (condensed tannins) is regulated by MYB-bHLH-WDR (MBW) transcription factor complexes in all angiosperms studied to date. Tr-MYB133 and Tr-MYB134 were isolated from T. repens and encode R2R3-MYBs that antagonize the activity of MBW activation complexes. These two genes are conserved in other legume species, and form two sub-clades within the larger anthocyanin/proanthocyanidin clade of MYB repressors. However, unlike petunia and Arabidopsis, these R2R3-MYB repressors do not prevent ectopic accumulation of anthocyanins or proanthocyanidins. Instead, they are expressed when anthocyanins or proanthocyanidins are being synthesized, and provide feedback regulation to MBW complexes. This feedback occurs because Tr-MYB133 and Tr-MYB134 are themselves regulated by MBW complexes. Tr-MYB133 is regulated by MBW complexes containing anthocyanin-related R2R3-MYB proteins (Tr-RED LEAF), while Tr-MYB134 is regulated by complexes containing the proanthocyanidin R2R3-MYBs (Tr-MYB14). Other features of the MBW gene regulation networks are also conserved within legumes, including the ability for the anthocyanin MBW complexes to activate the expression of the AN1/TT8 clade bHLH factor. The regulation of Tr-MYB133 and Tr-MYB134 by distinct, pathway-specific MBW complexes has resulted in subspecialization for controlling anthocyanin or proanthocyanidin synthesis.